COMMUNITY POLICING STRATEGY POLICY EVALUATION IN THE DIRECTORATE OF COMMUNITY DEVELOPMENT CENTRAL SULAWESI REGIONAL POLICE - Ariadisalam; Moh. Irfan Mufti; Munari (RADJA PUBLIKA, 2025)
Ariadisalam, Stambuk Number. B 102 24 059, with the research title Evaluation of Community Policing Strategy Policy at the Directorate of Community Development of the Central Sulawesi Regional Police, guided by Moh. Irfan Mufti and Munari. This study aims to evaluate the implementation of the Community Policing Strategy Policy at the Directorate of Community Development of the Central Sulawesi Regional Police in preventing and maintaining security and order through the partnership of the Indonesian National Police and the community. This study uses a qualitative descriptive research method. The theory used in this study is the evaluation theory of the CIPP (Contex, Input, Process, Product) model proposed by D. Stufflebeam (in Ibrahim). The informants in this study amounted to 7 (seven) people. The data obtained in this study are from observations, interviews, and documentation. The data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion/Verification. The results of this study show that the implementation of the Community Policing Strategy Policy at the Directorate of Community Development of the Central Sulawesi Regional Police has not run optimally as seen in all evaluation dimensions. In terms of contextual dimensions, it is still found that the public's understanding of policy intentions and objectives is not evenly distributed, so that community participation has not been fully realized. In the input dimension, obstacles also arise due to limited budget support, the number of personnel, and facilities and infrastructure that function as supporting media for the implementation of tasks. Meanwhile, from the process aspect, the implementation of various activities aimed at supporting the creation of policy goals has not been able to reach all levels of society and there are still people who are reluctant to communicate and interact with the National Police because there is still a stigma attached that the National Police is an organization that is synonymous with arrogant repressive efforts. As a result, in the product dimension, the ultimate goal of the Community Policing Strategy Policy, namely the establishment of an effective partnership between the National Police and the community in realizing security and order, has not been realized optimally. In terms of sustainability, the results of the study show that this policy needs to be continued but accompanied by a readjustment to the dynamics of the current situation.